Low-Iodine Diet of 4 Days Is Sufficient Preparation for 131I Therapy in Differentiated Thyroid Cancer Patients - Dekker, Bernadette L; Links, Mirthe H; Muller Kobold, Anneke C; Swart-Busscher, Linda G; Kars, Marleen; Bons, Judith A P; Brouwers, Adrienne H; Links, Thera P; van der Horst-Schrivers, Anouk N A (The journal of clinical endocrinology and metabolism, 2022)
Abstract Context No consensus exists about the optimal duration of the low-iodine diet (LID) in the preparation of 131I therapy in differentiated thyroid cancer (DTC) patients. Objective This work aimed to investigate if a LID of 4 days is enough to achieve adequate iodine depletion in preparation for 131I therapy. In addition, the nutritional status of the LID was evaluated. Methods In this prospective study, 65 DTC patients treated at 2 university medical centers were included between 2018 and 2021. The patients collected 24-hour urine on days 4 and 7 of the LID and kept a food diary before and during the LID. The primary outcome was the difference between the 24-hour urinary iodine excretion (UIE) on both days. Results The median 24-hour UIE on days 4 and 7 of the LID were not significantly different (36.1 mcg [interquartile range, 25.4-51.2 mcg] and 36.5 mcg [interquartile range, 23.9-47.7 mcg], respectively, P = .43). On day 4 of the LID, 72.1% of the DTC patients were adequately prepared (24-hour UIE < 50 mcg), and 82.0% of the DTC patients on day 7 (P = .18). Compared to the self-reported regular diet, DTC patients showed a significantly (P < .01) lower percentage of nutrient intake (calories, protein, calcium, iodine, and water) during the LID. Conclusion The 24-hour UIE on day 4 of the LID did not differ from day 7, and therefore shortening the LID from 7 to 4 days seems justified to prepare DTC patients for 131I therapy in areas with sufficient iodine intake and may be beneficial to maintain a sufficient nutritional intake during DTC treatment.